(untitled) (Hekima Review, 2016)
This paper aims at establishing how the family of Nazareth can be a model for today’s Christian families with regard to the law observance. It uses an intercultural approach. This will consist of analysing the family values as stipulated in the Congolese Family Code, those exemplified by the family of Nazareth (Luke 2:21-52), and those set in the Catholic Church. the paper will conclude by summarizing the similarities and diferences between a contemporary family, a biblical family and a Catholic Church family but also by indicating the way forward regarding the respect of family code.